Youth radicalization in Cabo Delgado: Root causes, triggers and drivers of Mozambique's jihadist insurgency - Dörhage, Friederike Germaine Marie Savatier (2022)
Since October 2017, Cabo Delgado, Mozambique’s most northern province, has been destabilized by the emergence of a jihadist group named Ahlu-Sunnah Wa-Jama (ASWJ). The group’s emergence had profound implications for the Southern African region, bringing an end to an era of peace and stability, in the only African region so far unaffected by terrorism. This dissertation thoroughly analyzes ASWJ’s inception and development by answering the following research question: Which factors brought the youth to radicalize in Cabo Delgado and what drivers have allowed the insurgency to prosper until now? Fundamentally, this dissertation analyzes the root causes, triggers and drivers of the insurgency by taking a chronological approach, which allows for the deconstruction of each individual layer accounting for the current status quo. The purpose of this dissertation is to create a solid and all-encompassing understanding of the reasons behind the conflict, an essential milestone to future research on potential peacebuilding solutions. Such an approach is needed as the existing literature on the subject has until this point focused on analyzing the root causes of the conflict or the triggers separately, not allowing for a more complete picture of the conflict. This dissertation seeks to close this gap by deconstructing and linking all existing layers. In order to achieve this goal, this research project adopts an interpretivist research philosophy and resorts to qualitative methods.